The Quality of Taxonomy Translation in English Indonesian Latin by Biological Education Students - Allif Syahputra Bania*; Nuraini Nuraini; Nursamsu Nursamsu; Muhammad Yakob (Jurnal Pendidikan Sains Indonesia, 2021)
Translation of literacy in english, Indonesian and latin has a strategic position in the biological sciences that must be studied with good quality for students so that the development of science. The purpose of this study is to examine the quality of taxonomy translation in English, Indonesian and Latin with regard to biology education. This research is a quantitative-descriptive research. The test method is used to collect data on the ability to translate in biology education learning by using the google form media provided through the biology student WhatsApp group due to the Covid-19 pandemic in the form of 10 questions with a blend of English, Latin and Indonesian about taxonomy. There are 13 respondents who are ready to answer the test. The test is given for 1 credit which is about 45 minutes as the deadline. The data analysis technique in this study is descriptive quantitative which uses three lines of research activities, namely data reduction, data display, and conclusion drawing/verification.The results obtained by respondents find it easier to translate test questions in short sentences. The quality of taxonomy translations related to English, Indonesian and Latin have good quality because from the first session, namely translation into the target language English, 4 of the total questions were obtained with the percentage of success by students in translating well above 50%. Likewise for the results of the translation with the target language Indonesian, the respondents managed to answer all questions well with a percentage above 50%. Here it can be seen that, translating into the target language Indonesian is still easier for respondents to produce because all questions are of high value than translating into the target language English.